2020
DOI: 10.1002/pbc.28318
|View full text |Cite
|
Sign up to set email alerts
|

How young patients with cancer perceive the COVID‐19 (coronavirus) epidemic in Milan, Italy: Is there room for other fears?

Abstract: The rapid spread of coronavirus disease 2019 epidemic in Italy, in particular in the Milan focal point, required drastic measures and led to panic in the population. While in our center we did not change our approach to the treatment of our young patients with cancer, we developed a qualitative survey to assess their perception of the risk and level of stress. The survey showed that a relatively large proportion of young patients felt personally at risk of severe complications. We believe that we need to adequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
101
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(116 citation statements)
references
References 15 publications
(45 reference statements)
3
101
0
1
Order By: Relevance
“…A recent study of Italian adolescent patients with cancer and survivors revealed that both groups worried about contracting the virus and felt personally at risk for severe complications, with survivors reporting more worry than those in follow-up care. 31 When stratified by treatment status, our results revealed the highest levels of anxiety in those who had completed treatment within the past 6 months, who were followed by those in treatment at the time of the study. We speculate that this may in part be due to the uncertainty often experienced upon treatment completion, when individuals often have to wait for scans before remission can be confirmed.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…A recent study of Italian adolescent patients with cancer and survivors revealed that both groups worried about contracting the virus and felt personally at risk for severe complications, with survivors reporting more worry than those in follow-up care. 31 When stratified by treatment status, our results revealed the highest levels of anxiety in those who had completed treatment within the past 6 months, who were followed by those in treatment at the time of the study. We speculate that this may in part be due to the uncertainty often experienced upon treatment completion, when individuals often have to wait for scans before remission can be confirmed.…”
Section: Discussionmentioning
confidence: 66%
“…Unlike Italian adolescents, 31 our AYA participants consumed most of the news related to the pandemic via general news sources, which were followed by social media outlets. This difference may be due to the older age of our sample.…”
Section: Discussionmentioning
confidence: 99%
“…There has been some epidemiologic investigation into the perceived risk and anxiety regarding the pandemic in pediatric oncology patients. In a survey of young cancer patients in Milan, a large proportion of them felt “personally at risk of severe complications.” SIOP, St Jude, the American Society of Hematology, and others are developing a new platform for sharing resources and experiences in the evolving time of this global pandemic 2,10 . It will be important to continue sharing case information and conducting additional research in the coming years.…”
mentioning
confidence: 99%
“…The scientific literature is already reporting on the psychological fallout on the general population of the pandemic and the collective measures taken to contain it. The effects include rising levels of demoralization, anxiety, despair, depression, and sleep disorders, and there is a risk of a worsening mental health in patients with psychiatric disorders 2‐7 …”
mentioning
confidence: 99%